Purchase Intention of Electric Vehicles among Generation Z Consumers in Batam City - Lily Purwianti; Winston Winston; Hepy Hefri Ariyanto; Edy Yulianto Putra (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the factors influencing Electric Vehicle (EV) purchase intention among Generation Z consumers in Batam City, focusing on perceived risk, perceived value, and government support, with attitude as a mediating variable. Research Methodology: This study was conducted in Batam, Indonesia, using a quantitative approach. Data were collected through a survey of 461 Generation Z respondents in Indonesia. The study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software to analyze the relationships between variables. Results: The findings revealed that attitude is the most dominant factor directly influencing EV purchase intention. Government support and perceived value have a positive and significant effect on attitude, whereas perceived risk does not significantly influence attitude or purchase intention. Conclusions: The study concludes that building positive attitudes is key to increasing EV purchase intentions among Generation Z. This can be achieved by enhancing perceived value and providing clear and supportive government policies. Limitations: This study is limited by its geographic focus on Batam, which restricts the generalizability of the findings to other regions with different market dynamics and policy environments. Additionally, the use of cross-sectional data captures consumer perceptions at a single point in time, despite being dynamic. Contributions: This study contributes to the literature on consumer behavior and sustainable transportation, particularly in developing countries, and provides practical insights for policymakers and industries to accelerate EV adoption among younger consumers.